Pengaruh Tingkat Pertumbuhan Tabungan, Tingkat Suku Bunga Kredit dan Kecukupan Modal Terhadap Profitabilitas Lembaga Perkreditan Desa di Kecamatan Penebel Tabanan - INDAH LESTARI, NI PUTU MAWAR; Kusumawati, Ni Putu Ayu (UNHI Press, 2025)
The purpose of this research is to examine how factors like capital adequacy, deposit growth rate, and credit interest rate affect the profitability of LPDs in Tabanan's Penebel District. This research aims to shed light on the elements that impact LPDs' financial success and provide future management advice based on what we learn. A quantitative strategy based on multiple linear regression analysis approaches is used in the study procedure. All LPDs registered in Penebel District make up the population, and 132 LPDs were selected for the research. Secondary data culled from LPD yearly reports is what's utilised. While the research found no significant influence of credit interest rate or capital adequacy on LPD profitability, savings growth rate did have a positive and statistically significant effect.